Nest attentiveness drives nest predation in arctic sandpipers. Issue 10 (8th July 2020) - Meyer, Nicolas; Bollache, Loïc; Dechaume‐Moncharmont, François‐Xavier; Moreau, Jérôme; Afonso, Eve; Angerbjörn, Anders; Bêty, Joël; Ehrich, Dorothée; Gilg, Vladimir; Giroux, Marie‐Andrée; Hansen, Jannik; Lanctot, Richard B.; et al.
Abstract : Most birds incubate their eggs to allow embryo development. This behaviour limits the ability of adults to perform other activities. Hence, incubating adults trade off incubation and nest protection with foraging to meet their own needs. Parents can either cooperate to sustain this tradeoff or incubate alone. The main cause of reproductive failure at this reproductive stage is predation and adults reduce this risk by keeping the nest location secret. Arctic sandpipers are interesting biological models to investigate parental care evolution as they may use several parental care strategies. The three main incubation strategies include both parents sharing incubation duties ('biparental'), one parent incubating alone ('uniparental'), or a flexible strategy with both uniparental and biparental incubation within a population ('mixed'). By monitoring the incubation behaviour in 714 nests of seven sandpiper species across 12 arctic sites, we studied the relationship between incubation strategy and nest predation. First, we described how the frequency of incubation recesses (NR), their mean duration (MDR), and the daily total duration of recesses (TDR) vary among strategies. Then, we examined how the relationship between the daily predation rate and these components of incubation behaviour varies across strategies using two complementary survival analysis. For uniparental and biparental species, the daily predation rate increased with the daily total duration of recesses and with the mean duration of recesses. In contrast, daily predation rate increased with the daily number of recesses for biparental species only. These patterns may be attributed to two independent mechanisms: cryptic incubating adults are more difficult to locate than unattended nests and adults departing the nest or feeding close to the nest can draw predators' attention. Our results demonstrate that incubation behaviour as mediated by incubation strategy has important consequences for sandpipers' reproductive success.